Optimal Bypass and Cream Skimming - Laffont, Jean-Jacques; Tirole, Jean (American Economic Review, 1990)
This paper develops a normative model of regulatory policy toward bypass and cream skimming. It analyzes the effects of bypass on second-degree price discrimination, on the rent of the regulated firm, and on the welfare of low-demand customers. It shows that pricing under marginal cost may be optimal for the regulated firm, excessive cream skimming occurs if access to the bypass technology is not regulated, and the prohibition of bypass may increase or decrease the regulated firm's rent.